2015
DOI: 10.1016/j.cgh.2014.04.014
|View full text |Cite
|
Sign up to set email alerts
|

Fibrosis Progression in Nonalcoholic Fatty Liver vs Nonalcoholic Steatohepatitis: A Systematic Review and Meta-analysis of Paired-Biopsy Studies

Abstract: Background & Aims Little is known about differences in rates of fibrosis progression between patients with nonalcoholic fatty liver (NAFL) vs nonalcoholic steatohepatitis (NASH). We conducted a systematic review and meta-analysis of all studies that assessed paired liver biopsies to estimate the rates of fibrosis progression in patients with NAFLD including NAFL and NASH. Methods Through a systematic search of multiple databases and author contact, up to June 2013, we identified studies of adults with NAFLD … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

24
1,204
6
63

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 1,413 publications
(1,297 citation statements)
references
References 51 publications
24
1,204
6
63
Order By: Relevance
“…This conclusion has been further corroborated by the results of a recent meta-analysis looking at rates of fibrosis progression in 411 patients with NAFLD who had paired liver biopsies 13 .…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 66%
See 1 more Smart Citation
“…This conclusion has been further corroborated by the results of a recent meta-analysis looking at rates of fibrosis progression in 411 patients with NAFLD who had paired liver biopsies 13 .…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 66%
“…Since the data discussed above [10][11][12][13] indicates that, contrary to popular belief, there is an important risk of progression with NAFL to more serious fibrotic liver disease over time, we suggest it is now an appropriate time to consider changing the focus of the primary endpoint used in therapeutic trials for NAFLD, be it pharmacologic, life-style 14 or surgical 15 . The aim of the primary care physician and the metabolic clinician at least, needs to focus on prevention or reversal of early disease.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 88%
“…We used an RIPK3 antibody from ProSci, which was validated using RIPK3-deficient liver tissues, and mouse embryonic fibroblasts. (2,3) Although Dara et al used the same antibody as we did, it is unclear why they failed to detect RIPK3 in the liver. Another finding from the study by Dara et al was that RIPK1 acted upstream of c-Jun N-terminal kinase (JNK).…”
Section: To the Editormentioning
confidence: 85%
“…(2) This is in line with the systematic review and meta-analysis of paired biopsy studies published by Singh and coworkers, where there was no association between baseline severity of necroinflammation and risk of progressive fibrosis. (3) With all this taken into account, we argue that NAS is not only imperfect as a predictor of mortality but probably also insignificant and that fibrosis stage is the most robust marker for prediction of overall mortality in NAFLD. What we need are larger clinical relevant cohort studies of NAFLD patients with liver histology to finally resolve what histopathological patterns actually predict outcome.…”
Section: Replymentioning
confidence: 85%
“…In contrast to previous notions that NAFL did not cause serious chronic liver disease, increasing evidence is now showing that NAFL is not harmless. Recently it has been shown that NAFL is an important risk factor for the development of clinically relevant liver fibrosis [8][9][10][11] and consequently it is now being realized that it is important to understand what interventions and treatments are effective for decreasing liver fat [12] within the spectrum of liver disease in NAFLD.…”
Section: Introductionmentioning
confidence: 99%